Ex situ and in situ sensitized quantum dot solar cells. Issue 2 (18th November 2016) - Szemjonov, Alexandra; Ithurria, Sandrine; Dubertret, Benoit; Ciofini, Ilaria; Labat, Frédéric; Pauporté, Thierry
Abstract : Although quantum dot‐sensitized solar cells (QDSCs) prepared with in situ sensitized wide‐band gap semiconductor nanorods are commonly reported, very few examples of the ex situ sensitization of these nanorods are known. They usually result in poor solar cell performance parameters. In this work, we have tested the photovoltaic application of both ex situ and in situ sensitized ZnO nanorods by linker‐assisted attachment and by the successive ionic layer adsorption and reaction (SILAR) technique, respectively. For the ex situ sensitization, instead of classical spherical QDs, we used quasi two‐dimensional CdSe nanoplatelets (NPLs) of controlled thicknesses, the photovoltaic application of which has never been reported before. Regarding the in situ sensitization, the photoanodes were characterized by XRD, UV–VIS absorption, and Raman spectroscopy during deposition, which helped to better understand the formation of CdSe QDs nanostructured ZnO surface. Devices incorporating in situ sensitized ZnO nanorods demonstrated superior performance compared to the best measured efficiencies of QDSCs prepared with ex situ sensitization, and their J – V characteristics were more reproducible.